PERLINDUNGAN HUKUM BAGI TENAGA KERJA DENGAN STATUS PERJANJIAN KERJA WAKTU TERTENTU (PWKT) BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA - Pulungan, Ishar (Jurnal Jendela Hukum, 2023)
This paper discusses the Legal Protection for workers with the status of a Specific Time ork Agreement according to Law Number 11 of 2020 concerning Job Creation. Certain time work agreements are considered to be a lot of problems between workers and ompanies, especially in terms of contracts that should have switched status from a specific time work agreement (PKWT) to an indefinite time work agreement (PKWTT). So ar, the Specified Time Work Agreement (PKWT) is regulated in Law Number 13 of 2003 concerning Manpower, but with the passing of Law Number 11 of 2020 concerning Job reation, there have been many pros and cons, especially in terms of Specified Time Work Agreements (PKWT). The purpose of this research is to find out about legal protection for aborers with PKWT status based on Law Number 13 of 2003 and law no 11 of 2020. The esearch conducted in this journal uses normative juridical research. The government rgues that the new rules contained in Law Number 11 of 2020 to protect workers' rights also minimize disputes between workers and companies, but from the workers' side, they hink that this new law is oppressive to workers, especially in the specific time work greement (PKWT) section. So far, workers who are bound by a certain time work agreement still have hope to be contracted permanently if they are contracted for more than 3 years by the company, but in the Job Creation Law, workers with a certain time work agreement can be contracted continuously forever.